Low‐Dose Cyclosporine A in the Treatment of Severe Atopic Dermatitis Complicated by Chronic Hepatitis C Virus Infection. Issue 3 (6th April 2017) - Gnarra, Maria; De Simone, Clara; Garcovich, Matteo; Garcovich, Simone
Abstract: Atopic dermatitis (AD) is the most frequent chronic inflammatory skin disorder in children and is usually accompanied by genetic and environmental factors. Effective management and treatment of AD is challenging and often requires systemic immunosuppressive therapy when refractory to topical treatments. We report a rare association between chronic hepatitis C virus (HCV) and severe AD, management of which required systemic cyclosporine because of its favorable effects on inflammatory and viral‐related clinical outcomes.